Geneticizing Ethnicity and Diet: Anti-doping Science and Its Social Impact in the Age of Post-genomics - Hyun, Jaehwan (Frontiers in Genetics, 2017)
While gene doping and other technological means of sport enhancement have become a topic of ethical debate, a major outcome from genomic research in sports is often linked to the regulation of doping. In particular, researchers within the field of anti-doping science, a regulatory science that aims to develop scientific solutions for regulating doped athletes, have conducted genomic research on anabolic-androgenic steroids. Genomic knowledge on anabolic-androgenic steroids, a knowledge base that has been produced to improve doping regulation, has caused the ‘geneticization’ of cultural objects such as ethnic identities and dietary habits. Through examining how anti-doping genomic knowledge and its media representation unnecessarily reify cultural objects in terms of genomics, I argue that Ethical, Legal, and Social Implications (ELSI) research programs in human enhancement should include the social impacts of anti-doping science in their discussions. Furthermore, this article will propose that ELSI scholars begin their academic analysis on anti-doping science by engaging with the recent ELSI scholarship on genomics and race and consider the regulatory and political natures of anti-doping research.